Theocentric Ecology in Ibn Kathlr's Interpretation of the Taskhlr Term in QS. 16:14 Toward an Ethical Foundation for Marine Conservation - Alif, Billy Muhammad; Zain, Muhammad Irfan (QiST: Journal of Quran and Tafseer Studies, 2026)
Global and national marine ecological crises, particularly coastal degradation and water pollution in areas such as the southern coast of West Java, demand a comprehensive approach rooted not only in technical regulations but also in strong theological foundations. Contemporary environmental policies often experience a gap in integrating orthodox spiritual values, resulting in a lack of sociological resonance among Muslim communities. Modern ecotheology studies tend to use liberal hermeneutic approaches that often reduce the authenticity of classical exegesis. Therefore, this study aims to actualize the concept of taskhir (the subjugation of nature) in Ibn Kathir's exegesis of Surah An-Nahl verse 14 as a marine conservation ethical framework aligned with the pure understanding of the salaf generation. This research seeks to answer three main questions: (1) What is the textual analysis of QS. An-Nahl: 14 in Ibn Kathir's Tafsir? (2) What is the philosophical essence of the Taskhir concept according to the salaf understanding? and (3) How is the practical actualization of this concept within the marine conservation framework in Indonesia? Using a qualitative library research method with a tahlili exegesis approach, this study analyzes the linguistic structure and theological meaning of the verse through primary literature and a systematic review of reputable journals. The main findings indicate that theologically, the sea is subjugated by Allah, not absolutely conquered by humans (deconstructing anthropocentrism). The utilization of marine resources for both food (lahman tariyyah) and aesthetics (hilyah) is strictly bound by moral prerequisites in the form of gratitude and the prohibition of fasad (destruction). The Result affirms that the salaf's understanding of ecology is theocentric, where marine conservation is not merely a secular ecological demand, but a manifestation of monotheism and worship. Actualizing these values provides an essential philosophical and ethical foundation for marine spatial planning policies (RZWP3K) and sustainable coastal management.